Radical scavenging activity and cholinesterase inhibitory activity ofLeopoldia comosa (L.) bulbs - Loizzo, M.R.; Tundis, R.; Menichini, et al., F. (Progress in Nutrition, 2011)
SummaryLeopoldia comosa is a spontaneous plant growing in all Mediterranean area, including Calabria, where its bulbs (known as “cipudizze”) were used in traditional gastronomy and used flavoured with garlic, chilli pepper, or fried with potatoes (1,2). Bulbs (300 g) were extracted with EtOH through maceration. In order to operate a separation of lipo-philic compounds, the total extract was solubilized with MeOH/H2O (8:2) and extracted with n-hexane. The ethanol extract showed a total phenols content of 56.6 mg chlorogenic acid equivalent per g of extract and a flavonoids content of 23.4 mg quercetin equivalent per g of extract. Ethanol extract demonstrated the strongest radical scavenging activity with an IC50 value of 40.9 mg/ml. Alzheimer’s disease (AD) is the most common form of neurodegenerative disorders. Actually, AD treated by the use of agents which restore the level of acetylcholine through inhibition of both two major forms of cholinesterase: acetylcholine-sterase (AChE) and butyrylcholinesterase (BChE). n-Hexane extract exhibited the highest bioactivity tested using Ellman’s method (3) with IC50 values of 104.9 and 128.1 mg/mL for AChE and BChE, respectively. Attività radical scavenging e inibizione delle colinesterasi dei bulbi di Leopoldia comosa (L.)RiassuntoLeopoldia comosa è una pianta spontanea dell’area Mediterranea che cresce anche in Calabria dove i suoi bulbi sono noti come “cipudizze” ed utilizzati nella tradizione gastronomica insaporite con aglio, peperoncino o fritte insieme alle patate (1,2). I bulbi (300 g) sono stati sottoposti ad estrazione per macerazione con EtOH. Con lo scopo di isolare la frazione lipofilica, l’estratto totale è stato solubilizzato in MeOH/H2O (8:2) e estratto con n-esano. L’estratto etanolico dei bulbi presenta un tenore in fenoli totali di 56.6 mg di equivalenti di acido clorogenico per g di estratto, mentre il contenuto in flavonoidi è di 23.4 mg di equivalenti di quercetina per g di estratto. L’estratto etanolico presenta la maggiore attività radical scavenging con un valore di IC50  di 40.9 μg/mL. Il morbo di Alzheimer (AD) è il più comune disordine neurodegenerativo dell’età senile. Ad oggi l’unico trattamento per l’AD è basato su farmaci che possano mantenere adeguati livelli di acetilcolina circolanti e tali sostanze agiscono attraverso l’inibizione delle due maggiori forme di colinesterasi: acetilcholinesterasi (AChE) and butirilcholinesterasi (BChE). L’estratto in n-esano dei bulbi, testato attraverso l’Ellman’s method (3), ha mostrato una potente attività inibitoria con valori di IC50 di 104.9 e 128.1 μg/mL per AChE e BChE, rispettivamente.